The Influence Of Tax Knowledge, Taxpayer Awareness, Tax Sanctions And Love Of Money On Motor Vehicle Taxpayer Compliance - Monica Ganti Sari; Ahmad Junaidi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to look at the effect of tax knowledge, taxpayer awareness, tax sanctions and love of money on motor vehicle taxpayer compliance in the village of guru agung II, north kaur sub-district, kaur district, Bengkulu. This study uses quantitative methods of primary data, data collection methods using questionnaires. The population in this study were taxpayers in guru agung II village, totaling 173 households. This study uses purposive sampling technique. The sample in this study amounted to 173 samples, where the entire population was sampled. The data analysis technique used SPSS 26 (Statistical Product & Services Solution). The results showed that tax knowledge has no significant effect on motor vehicle taxpayer compliance. Taxpayer awareness has a positive and significant effect on motor vehicle taxpayer compliance. Tax sanctions have no significant effect on motor vehicle taxpayer compliance. Love of money has a positive and significant effect on motor vehicle taxpayer compliance. Tax Knowledge, Taxpayer Awareness, Tax Sanctions and Love Of Money have a positive and significant effect together on Motorized Vehicle Taxpayer Compliance.